Características histológicas de la dentina bovina mediante tinción Tricrómica de Masson - Lezcano, Melisa Raquel (2023)
Objectives: Identify the histological characteristics of bovine dentin using histological technique by decalcification with Masson's Trichrome staining. Materials and Methods: This was an observational and descriptive study using units of analysis. Bovine teeth were used, which were subjected to a decalcification technique and Masson's trichrome staining. Microscopic observation and registration of the structures was carried out. Results: In the microscopic observation of the teeth subjected to decalcification, dentin, predentin and the structural organization of the tubular and peritubular dentin were observed. The odontoblasts arranged in a palisade with the odontoblastic process included within the dentinal tubule and the periprocedural space. The presence of interglobular dentin is not observed in areas of coronary dentin. The histomorphological pattern corresponding to dentin-predentin-pulp is arranged in a similar way to human teeth. Conclusions: Bovine dentin constitutes an ideal substrate for in vitro research work with dental biomaterials, since it presents histological characteristics similar to bovine teeth; the absence of interglobular dentin would not represent a significant difference according to what was observed in this study.